Project-Based Deep Learning in Distance Education: Bridging Theory and Practice through a Systematic Literature Review - Amalia Sapriati; Maya Puspitasari; Fitria Amastini; Monika Handayani (International Journal of Educational Practice and Policy, 2026)
Project-Based Deep Learning (PjBDL) is an educational methodology that integrates the Deep Learning (DL) approach with Project-Based Learning (PjBL) principles. This systematic literature review seeks to offer a thorough examination of the theoretical underpinnings, instructional models, and practical implementations of PjBL within the field of deep learning and open and distance education (ODE). This review analysed 37 peer-reviewed articles retrieved from three reputable journal databases to assess their application across many sectors and regions worldwide, thereby underpinning PjBDL. The results indicated that the methodology holds significant potential for enhancing comprehensive student learning in both face-to-face and blended educational environments. Specifically, the review identified three principal themes: (1) PjBL is grounded in constructivist, experiential, and authentic learning theories and operationalised through instructional-design models such as ASSURE, Kemp’s model, SEIE, and POPBL; (2) deep learning is expressed across four interrelated dimensions—self-regulation, metacognition, conceptual understanding, and reflective learning; and (3) effective adaptation to ODE depends on technology-enhanced platforms as structural enablers, intentionally scaffolded instructional design, and the management of persistent barriers, namely technological readiness, instructor workload, process-level assessment, and digital inequality. Despite the insufficient research on fully online and distance learning, the pedagogical methodologies and frameworks examined in this review are beneficial for transforming PjBDL in terms of student autonomy, digital readiness, instructional design, and evaluation. This paper provides evidence-based techniques and practical recommendations for implementing PjBDL in remote educational institutions.